Glomerulonefritis Akut - Mutia Rahmah Siregar; Rahmawati Rahmawati (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Acute glomerulonephritis (AGN) is a sudden inflammation of the glomeruli in the kidneys, commonly triggered by an immunologic reaction to bacterial or viral infections, especially group A beta-hemolytic Streptococcus. AGN is most frequently found in children aged 2–10 years, with a higher prevalence in males. One of the most typical forms is post-streptococcal glomerulonephritis (PSGN), which appears approximately 1–2 weeks after a pharyngeal or skin infection. The pathogenesis of PSGN involves immune complex formation and complement activation, leading to glomerular injury characterized by hematuria, proteinuria, edema, and hypertension. Diagnosis is based on clinical symptoms, laboratory findings such as elevated ASO titers and decreased C3 levels, and occasionally renal biopsy. Management of PSGN is primarily supportive, including fluid restriction, diuretics, and antihypertensive therapy. In severe cases, corticosteroids, dialysis, or antibiotics may be necessary. The prognosis is generally favorable with proper treatment, although complications such as hypertensive encephalopathy and acute kidney injury may occur. Therefore, early detection and adequate management are crucial to prevent disease progression.